The future of hybrid ablation: an emerging need for an anticoagulation protocol for thoracoscopic ablation - Osmancik, Pavel; Budera, Petr (Journal of thoracic disease, 2017)
The midterm efficacy of hybrid ablation of atrial fibrillation (AF) reported in recent papers is about 70% in terms of sinus rhythm maintenance without antiarrhythmic drugs. Bearing in mind that the majority of patients enrolled are patients with persistent and long-standing persistent AF, the reported efficacies seem to be very good. Despite the high efficacies, safety remains a critical issue in hybrid, and especially thoracoscopic ablations. The frequency of complications during thoracoscopic ablations is more than 10% in the majority of reports. Most are short-term with no sequelae (such as pneumothorax or pneumonia); however, life-threatening complications have also been described, e.g., a sternotomy in response to a laceration of the left atrium (LA). One of the most serious ablation complications is stroke. The rate of strokes, which has been reported during or shortly after thoracoscopic ablation, seems to be higher than the rate reported after catheter ablation. This is especially true in papers describing thoracoscopic ablations that were not immediately followed by a catheter ablation. A possible explanation is differences in anticoagulation management during the two procedures. During catheter endocardial procedures, a standard anticoagulation protocol exists and is routinely applied; however, there is no such set of recommendations for anticoagulation during the thoracoscopic-phase of an ablation. It seems probable that, in many cases, no anticoagulation is used during thoracoscopic ablations. Moreover, whatever anticoagulation protocol is used during thoracoscopic ablations often goes unreported. A discussion about the best anticoagulation strategy during thoracoscopic ablation is urgently needed. In the future, standards of anticoagulation during thoracoscopic ablation should be clearly reported, just as they are now for catheter ablations.
Keywords: thoracoscopic ablation; persistent atrial fibrillation (AF); Hybrid ablation; anticoagulation; long-lasting persistent atrial fibrillation (AF); stroke